Consumers’ Intention pada Omni-Channel Matahari dengan Pendekatan Utaut - Rani Normawati; Anna Widayani; Ika Rachmawati (PANDITA : Interdisciplinary Journal of Public Affairs, 2022)
Technological developments, especially in product marketing, are very diverse, for example omni-channel. Omni-channel is implemented to reach a wider audience. This study aimed to examine and analyze the factors influencing the intention to use omni-channel among Matahari Department Store (MDS) consumers. The collected data was processed based on the descriptive statistical analysis method to determine the characteristics of the respondents and inferential statistics using SEM-PLS. The results of the study show that performance expectancy has a positive effect on omni-channel shopping attitude. Likewise with the omni-channel shopping attitude towards consumers' intention. A positive but not significant effect can be seen in the relationship between the effect of effort expectancy and omni-channel shopping attitude.